A Social Class in Thomas Hardy’s The Mayor of Casterbridge - Abu Fanani; Muhammad Thoriqussuud; Fathur Rohim; Machfud Muhamad Sodiq; Akhmad Syaikhu (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study is about a social class that plays a very important role in the life and death of the main character in Thomas Hardy’s the Mayor of Casterbridge. It is called to have an important role as it triggers the character to survive though eventually; he must die for it. Using the capitalist mode of production and descriptive and dramatic approach to picture the social class in the society as well as the effect of it, the study shows that the main character’s life is triggered by the social class in the society, that is, wealth possession. The more property a man gets the more respects he gets from the society. On the contrary, the less property he gets the less respects he gets. It, then, becomes the main issue of the people in the novel to behave according to the social class driving the main character to the downfall. Finally, although the study has the novelty since no previous studies use the same theory as the researcher’s study, the study gives the readers moral lesson that sometimes in a society, wealth is worth more whilst in another society is not. Besides, this novelty is to develop the study of literature.